Moving beyond 'gender-neutral': creating gender expansive environments in early childhood education. Issue 1 (2nd January 2022) - Chapman, Rachel
ABSTRACT: In this research, feminist post-structuralism and queer theory were used to examine Australian early childhood educators' views on children's gender identity development, and the content on gender in the Australian Government's Early Years Learning Framework. The methodology and study design were based upon qualitative phenomenological research methods. The participants consisted of 12 early childhood educators who worked in kindergarten and long day care settings. The data was collected through semi-structured focus groups and semi-structured interviews. Feminist post-structuralist discourse analysis was used to identify discourses deployed within participants' responses in relation to how they may enable or constrain pro-diversity spaces. Implications of this research include the need for further support and guidance for educators through policy, curriculum, resources and teacher education. This research highlighted the need to trouble the notion of 'gender-neutral' and the value of fostering gender expansive environments in early childhood education.